The BCC-FCC Phase Transformation Pathways and Crystal Orientation Relationships in Dual Phase Materials From Al-(Co)-Cr-Fe-Ni Alloys - Hecht, Ulrike; Gein, Sergej; Stryzhyboroda, Oleg; Eshed, Eyal; Osovski, Shmuel (Frontiers in Materials, 2020)
The alloy system Al-(Co)-Cr-Fe-Ni contains compositional ranges where a solid state BCC-FCC phase transformation leads to dual-phase materials composed of face-centered cubic (FCC) and body-centered cubic (BCC) phases with nearly equal volume fraction. The microstructure arising from this transformation at slow cooling rates is the classical Widmanstätten structure, with FCC-laths and colonies growing from grain boundaries into the parent BCC-B2 grain. Very distinct microstructures are obtained, when Widmanstätten growth is kinetically suppressed e.g. during continuous cooling with high cooling rates. These novel microstructures are associated with the spinodal decomposition of the parent BCC-B2 such that FCC growth occurs during the spinodal decomposition or upon annealing from a metastable, fully spinodal state. We review the microstructures at case as function of the imposed cooling regimes for the Co-free medium entropy alloy AlCrFe2Ni2. One of them, termed ultrafine vermicular microstructure, involves a characteristic and novel crystal orientation relationship (OR) between FCC and BCC. We identify the common planes and directions of this OR using electron backscatter diffraction maps to be {111}^FCC∥{121 ̅ }^BCC and 〈1 ̅01〉^FCC∥〈1 ̅01 ̅ 〉^BCC, respectively. Embedded is a second OR with {13 ̅1 ̅ }^FCC∥{1 ̅03}^BCC and 〈101〉^FCC∥〈010〉^BCC. We further show that the vermicular FCC phase contains a high amount of lattice strain and sub-grain boundaries with disorientation angles in the range from 2 to 12°, as a result of the solid-state phase transformation.